WEIGHING APPLICATION FOR HIRE OF GOODS AIR CARGO WAREHOUSE IN GLOBAL PT. GAPURA ANGKASA USING MICROSOFT VISUAL BASIC 6.0 - Paramita Nilam K; Linda Wahyu Widianti, SKom, MMSI (Jurnal Sistem Informasi, 2005)
With advances in computer technology, companies could be eased with a variety of applications that help facilitate the work primarily on the company's shipments. This is because the company needs the data and information processing. Activities that are frequently encountered in the company and the services sector is the delivery of goods and cargo weighing of air cargo for storage. To provide information on items weighing optimal storage, you need a good handling in the processing. To achieve the desired results of good service and processing the data, so data weighing of cargo items to lease the warehouse can be processed in accordance with what we want. Therefore, the authors tried to make an application which can assist and accelerate the process of data processing company. With this application, is expected to report a problem controlling as well as the manufacture of goods for storage weighings can be done easily and more effectively in terms of time and funds.